Compositional Patterns of Ruderal Herbs in Santiago, Chile [Patrones Composicionales de Hierbas Ruderales en Santiago, Chile] - Castro-Morales, S (Universidad de Concepcion, 2015)
Fragmentation of the natural environment is a consequence of urbanisation. It impacts the biodiversity of native flora that characterises a region. This study focused on characterising the diversity, composition and distribution of native and alien ruderal species present in different suburbs of Santiago de Chile. We found that plant assemblages of ruderal species were characterised by a higher proportion of alien species (69 taxa), whose original distribution corresponds to the Mediterranean Basin (46 taxa), and a low representation of native species (14 taxa). The results show that the spatial distribution of weeds within Santiago was not random, because two clusters were found based on patterns of compositional similarity. Further research should be undertaken to determine the cause of this phenomenon that probably obeys historical and ecological factors such as the past use of soils or urban landscape ornamentation programs. © 2015, Universidad de Concepcion. All rights reserved.
Keywords: Alien plants; Native plants; Plant assemblages; Weeds